Quantity implicature interpretations in bilingual population: the case of Imbabura Kichwa - Gualapuro Gualapuro, Santiago David (Frontiers in Human Neuroscience, 2024)
Most studies on the pragmatic interpretation of existential quantifiers have been conducted in major Indo-European languages like English, Spanish, French, and Greek, focusing mainly on monolingual participants. However, in indigenous linguistic research, especially experimental research, it is crucial to consider several linguistic and extralinguistic factors for successful implementation. Our research centered on the experimental investigation of the pragmatic interpretation of the quantifier wakin, meaning some in Kichwa, with Kichwa-Spanish bilingual adults from the province of Imbabura Ecuador. We employed the Truth Value Judgement Task (TVJT) for our experiments and incorporated the explicit Question Under Discussion (QUD) paradigm to facilitate pragmatic interpretations among our participants. Our initial experiment revealed a 78% acceptance level for the pragmatic interpretation of "some, but not all" in Kichwa, significantly lower than the 95% acceptance range observed in other languages. We hypothesized that access to technology and formal education might influence these results, leading us to simplify our experiment by eliminating the technological components of the research. In our subsequent experiment, adult speakers of Imbabura Kichwa achieved a 97% accuracy level, comparable to speakers of other languages. To benchmark our results against speakers of other languages under similar conditions, we evaluated whether Spanish speakers from two varieties in Ecuador (Quito and Guayaquil) could generate the "some, but not all" scalar implicature with the Spanish quantifier algunos. Our findings indicated that speakers achieved 95.5% and 97.4% accuracy for both varieties, respectively. Therefore, this study infers that under optimal conditions, speakers of indigenous languages in rural communities demonstrate commendable performance in experimental linguistic studies. Nonetheless, it underscores the necessity for meticulous planning and distinct handling in experimental studies involving speakers of these languages residing in rural areas without access to technological elements. We propose that such research broadens our comprehension of language utilization in minority communities and positively influences language restoration efforts by expanding experimental linguistics studies to indigenous languages.